Rice Productivity Growth During Nine Years in Badung Regency, Bali Province - Anak Agung Keswari Krisnandika; I Made Anom Sutrisna Wijaya; I Gusti Agung Ayu Ambarawati; Anak Agung Ayu Mirah Adi; Eisaku Tamura; Chiharu Hongo (Hasanuddin University, 2019)
The trend of rice productivity and its stability in Badung Regency are presented in this study. The area is a tourism-based economy without leaving the role of rice production to feed the people. Time series data were collected from five sub districts covering 53 villages during 2008-2016 due to the completeness of the data. Variability of the data was observed from the coefficient of variance (C.V.) to decide rice productivity stability. This study also observed correlation between rainfall and rice productivity in the area. Result of the study shows that rice productivity trend in Badung Regency tend to decline during nine years of observation especially in 2014-2016. Three sub-districts had stable condition, while two sub-districts in tourism area contributed to the decline of this matter. Analysis using bi-plot revealed that there is no significant correlation between rainfall in sub-district and rice productivity, implying that water is available throughout the year. In terms of stability, majority of villages (69.81%) had stable condition of rice productivity ranging from middle and high category. Other 30.19% villages were categorized as unstable ranging from low to high productivity. This condition showed that Badung Regency were able to maintain stability of rice productivity during nine years of observation. Implication of this study is to pay more attention to two sub districts in tourism area to improve their rice productivity such as implementation of good agricultural practices.